2016
DOI: 10.26417/ejis.v4i1.p115-121
|View full text |Cite
|
Sign up to set email alerts
|

Research Concerning the Efficiency of Aronia Melanocarpa for Pharmaceutical Purpos

Abstract: The major impact of many types of disease on the human body have generated medical research orientation toward biotechnology identification and extraction of active principles from natural resources. The social problem to improve the health of the population, to maintain social balance of a healthy society oriented medical-pharmaceutical research for the use of other sources of pharmaceuticals from natural sources and not synthetic chemistry. On this line of work is also included the research wich orientates p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recent researches have focused attention on A. melanocarpa due to its numerous health benefits in a broad range of pathological conditions [12]. It has been reported that fruit and extracts of A. melanocarpa exert gastroprotective, hepatoprotective, antiinflammatory and antiproliferative activity [12,13]. Furthermore, the health-promoting effects of extracts of this plant involve antiatherosclerotic, antiplatelet and hypoglycemic properties [7,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent researches have focused attention on A. melanocarpa due to its numerous health benefits in a broad range of pathological conditions [12]. It has been reported that fruit and extracts of A. melanocarpa exert gastroprotective, hepatoprotective, antiinflammatory and antiproliferative activity [12,13]. Furthermore, the health-promoting effects of extracts of this plant involve antiatherosclerotic, antiplatelet and hypoglycemic properties [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the health-promoting effects of extracts of this plant involve antiatherosclerotic, antiplatelet and hypoglycemic properties [7,14]. Moreover, it was previously confirmed that A. melanocarpa extract may reduce systolic and diastolic pressure and be useful in the management of DM [5,13]. However, to our best knowledge, the effectiveness of A. melanocarpa extract in combination with different diet regimens in the treatment of MetS has been not investigated so far.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have focused attention on A. melanocarpa due to its numerous health benefits in a broad range of pathological conditions (Jurikova, 2017). It has been reported that fruit and extracts of A. melanocarpa exert gastroprotective, hepatoprotective, antiinflammatory and antiproliferative activity (Lupascu, 2016). Furthermore, 1,2,3 Abstract: This study summarizes the effects standardized Aronia melanocarpa extract (SAE) on different pathophysiological processes linked with cardiovascular system from both animal and human investigations.…”
Section: Discussionmentioning
confidence: 99%